Context-aware and self-adaptive trust model for pervasive computing - Jiang-tao WANG; Zhi-gang CHEN; Xiao-heng DENG (Tongxin xuebao, 2012)
To cope with the behaviour trust problems emerging at ve environments,a context-aware and selfadaptive trust model(CASATM) for pervasive environments was proposed,the trust model provided security protection based on service content adaptively at various level,nd be sensitive to contexts such as time,location and service content.A simple and efficient risk evaluation model was presented to initialize trust value to unknown entities which was a common phenomenon in pervasive environments.Simulation results testify to the contexts awareness of this model,as well as resistance of periodically cheating behaviour from malicious entity.